Avaliação ecotoxicológica de fármacos isolados e em mistura para organismos aquáticos - Santos, Aline Nunes dos (2021)
Pharmaceuticals are micropollutants widely used in the world. And over the last few decades consumption has been increasing, generating a great concern about the environmental risks that can be caused by such contaminants. However, a lack of data about the adverse effects of pharmaceuticals single or in complex mixture can underestimate the long-term effects that can occur in the aquatic ecosystems. Toxic effects of the pharmaceutical’s simvastatin, metformin, and clindamycin, isolated and in mixture were evaluated on zooplanktonic organisms Daphnia similis e Ceriodaphnia silvestrii. For this, acute and chronic toxicity tests were performed with isolated compounds. And for binary mixtures acute tests were performed. The results obtained in this study demonstrated that both D. similis and C. silvestrii were more sensible to a simvastatin when compared with the other pharmaceuticals are as follows: SIN>MET>CLI. The chronic toxicity data with C. silvestrii showed a statistically significant reduction in fertility when exposed to simvastatin, metformin, and clindamycin at concentrations of 20 µg/L, 6,4 mg/L and 20 mg/L, respectively. It was possible to describe toxicological interaction occurring between the pharmaceuticals in joint action synergism and antagonism, observed interactions level dependent and ratio dependent. In light of this, there is no doubt that the presence of pharmaceuticals in water matrices cannot be neglected. And the studies based on single toxic effects can underestimate the real impacts of environmental contaminants on aquatic ecosystems.